Novel effect of ezetimibe to inhibit the development of non‐alcoholic fatty liver disease in Fatty Liver Shionogi mouse. Issue 1 (19th March 2013) - Wang, Xiang; Sugimoto, Ken; Fujisawa, Tomomi; Shindo, Nobuyasu; Minato, Satomi; Kamada, Yoshihiro; Hamano, Mina; Ohishi, Mitsuru; Ikegami, Hiroshi; Rakugi, Hiromi
<x xml:space="preserve">Abstract</x> Aim Several studies using experimental non‐alcoholic fatty liver disease (NAFLD) models have shown that ezetimibe, an inhibitor of cholesterol absorption mainly in the intestine, not only protects against diet‐induced hyperlipidemia, but also attenuates liver steatosis. The aim of this study was to clarify whether ezetimibe inhibits the development of NAFLD and to elaborate the mechanism of ezetimibe to inhibit the development of NAFLD using Fatty Liver Shionogi (FLS) mice, a spontaneous model of NAFLD/non‐alcoholic steatohepatitis. Methods Male FLS mice at 20 weeks of age were divided into two groups (n = 7 in each group). Mice fed a normal laboratory chow, CRF‐1 or CRF‐1 containing 0.005% w/w ezetimibe (7 mg/kg per day) for 4 weeks. After 4‐week treatment with ezetimibe, the livers of each group of mice were subjected to histological as well as molecular evaluation. Results Ezetimibe administration for 4 weeks was associated with improvement of steatosis and fibrosis of the liver in normal diet‐fed FLS mice. Ezetimibe reduced hepatic reactive oxygen species generation and prevented ubiquitination and protein degradation of microsomal triglyceride transfer protein (MTP), a key molecule for very low‐density lipoprotein assembly and export, via downregulation of the protein expression of Skp2 and CDC20. Conclusion Ezetimibe not only reduced lipid synthesis in the liver, but also promoted lipid discharge from the liver by preventing post‐translational degradation of MTP via a reduction of hepatic reactive oxygen species generation, leading to inhibition of the development of NAFLD.